An Updated Genome Assembly Improves Understanding of the Transcriptional Regulation of Coloration in Midas Cichlid - Lv, Yunyun; Li, Yanping; Liu, Yi; Wen, Zhengyong; Yang, Yexin; Qin, Chuanjie; Shi, Qiong; Mu, Xidong (Frontiers in Marine Science, 2022)
Midas cichlid (Amphilophus citrinellus), a popular aquarium fish, attracts extensive attentions from worldwide biologists mainly due to its morphological polymorphism (dark versus gold). Continuous efforts have therefore been paid to address mechanisms of its coloration variants, while it is far away from detailed illustration of a clear regulatory network. Some limits may come from the absence of a high-quality genome assembly and a relatively accurate gene set. In this study, we sequenced about 149 Gb of nucleotide sequences of Midas Cichlid, generating a genome assembly with a total size of 933.5 Mb, which exhibits a good genome continuity with a contig N50 of 10.5 Mb. A total of 25,911 protein-coding genes were predicted and about 90% completeness was obtained, which may build a good gene bank for understanding expressional differences of color variation. With the final gene set, we identified a total of 277 differential expressional genes (DEGs), of which 97 up- and 180 down-regulated were determined in dark-vs-gold comparisons. Two protein-protein interaction (PPI) networks were constructed from these DEGs and three key functional modules were classified. Hub genes within each module were evaluated, and we found that the third key module contains tyrp1b, oca2, pmela, tyr and slc24a5, which are previously proved to be associated with melanin formation. Two down-regulated DEGs (myl1 and pgam2) in the first key module may be involved in muscle movement and spermatogenesis, implying that certain side effects could be resulted from the morphological polymorphism. The first key module, consisting of proteins encoded by up-regulated DEGs that were associated with MAPK signaling, Toll-like receptor signaling and gonadotropin-releasing hormone pathways, may contribute to a negative upstream regulation or downstream influence on melanin biosynthesis. Taken together, our new genome assembly and gene annotation of Midas cichlid provide a high-quality genetic resource for biological studies on this species, and the newly identified key networks and hub genes in dark-vs-gold comparisons enhance our understanding of the transcriptional regulatory mechanisms underlying coloration polymorphism in Midas cichlid.